Seismic Assessment and Retrofitting of Existing RC Building by Using Steel Braced Frames - Alhashimi, Ahmed Abdulbasit K. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Antakya city is in danger as a result of solid seismic actions happening in the territory, and diverse soil conditions that can create a variety of the ground motion amplification. In recent years, scientists and engineers have started to assess the existing structures and their behaviors in resistance to lateral loading, potential earthquake hazard, and vulnerability. Existing structures can be retrofitted to incorporate new improvements and techniques to oppose quake and seismic burdens, which was the most efficient approach to shield against the financial and social disaster influenced by serious seismic action in urban areas. This thesis presents a study on a five-storey reinforced concrete structure was built in 1988 and located in Antakya, Turkey. This work consists of three phases. The first stage, data collection which includes building plans, material properties, structural condition, and reinforcement details. Material properties are measured using non-destructive testing method called model calibration. The model calibration is obtained from building dominant periods and mode shapes of the existing building, which have been measured using forced vibration tests. In the second stage, the analytical modeling of the structure is made using SAP2000. After model calibration, the nonlinear static pushover analysis for the seismic performance evaluation based on the ATC-40 methods has been obtained. Finally, the existing building, which showed low performance according to code requirements, is strengthened by using two different types of external steel brace frames. They have been attached to Y-direction, which has poor performance for both sides until the second floor, and recommended that this strengthening technique is an appropriate method according to the performance and cost analysis. Keywords: Evaluation earthquake, Pushover analysis, Retrofitting, Forced vibration

ÖZ: Antakya ili, bölgede meydana gelen güçlü depremler ve zemin hareket büyütmesini meydana getirebilecek farklı zemin koşulları nedeniyle risk altındadır. Akademisyenler ve mühendisler son yıllarda mevcut binaları, deprem yüküne, potansiyel sismik tehlikeye, hassasiyete ve yanal yüklere karşı dirençteki performanslarını değerlendirmeye başlamışlardır. Günümüzde, mevcut binalar, kentsel ortamlarda şiddetli sismik aktiviteden etkilenen ekonomik ve sosyal felaketi önlemenin en ekonomik yolu olan, deprem ve sismik yüklere karşı direnç gösteren yeni gelişmeleri ve yöntemleri içerecek şekilde yeniden güçlendirilebilir. Bu tez, 1988 yılında inşa edilen ve Türkiye, Antakya'da bulunan beş katlı bir betonarme yapı ile ilgili yapılan çalışmayı sunmaktadır. Bu çalışma üç aşamadan oluşmaktadır. Bu aşamalar; ilk olarak, veri toplama (yapı planları, malzeme özellikleri, yapısal durum ve donatı detayları), malzeme özelliklerinin belirlenmesi için tahribatlı ve tahribatsız testlerin kullanılması, mevcut binaya zorlanmış titreşim uygulanarak bina hakim periyot ve mod şekillerinin belirlenmesi; Daha sonra, SAP2000 programı kullanarak yapının analitik modellemesinin yapılması ve model kalibrasyonundan sonra ATC-40 yöntemlerine dayanan sismik performans değerlendirmesi için doğrusal olmayan statik itme analizinin yapılması; Son olarak, performansı yetersiz bulunan mevcut binanın güçlendirilmesi için iki farklı tipte çelik çerçeve, binanın zayıf olduğu Y-yönünde ikinci kata kadar eklenerek güçlendirilmesi ve bu güçlendirme tekniğinin bina performansı ve fiyat analizi yönünden uygun bir yöntem olduğunun önerilmesi, kapsamaktadır. Anahtar Kelimeler: Deprem, Statik itme analizi, Güçlendirme, Zorlanmış titreşim
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2018. Supervisor: Assoc. Prof. Dr. Mehmet Cemal Geneş.
Keywords: Civil Engineering; Earthquake engineering; Earthquake--resistant construction--Resistant Design; Buildings--Retrofitting--Antakya (Turkey); Buildings--Safety measures; Evaluation earthquake; Pushover analysis; Retrofitting; Forced vibration